Targeting Microglia as a Therapeutic Approach to Treat Neuroinflammatory Disorders - Almalki, Masi (2025)
Neuroinflammation, a complex immune response within the central nervous system (CNS), contributes to neurodegenerative diseases. It is mediated predominantly by microglia, the brain's resident immune cells. Existing in vitro models, however, often fail to capture the human-specific characteristics of microglial behaviour, limiting the understanding of neuroinflammatory mechanisms and therapeutic intervention points. This thesis addresses these limitations by developing a human microglia model derived from peripheral blood mononuclear cells (PBMCs), offering a physiologically and human-relevant system for exploring microglial activation and signalling pathways central to neuroinflammation. The primary objective was to create and validate a reproducible differentiation protocol for microglia-like cells from PBMCs, confirmed through microglial markers and functional assays that mimic primary microglial responses. This model was then applied to investigate how damage-associated molecular patterns (DAMPs), such as adenosine triphosphate (ATP), influence microglial activation via P2 receptors (P2X4 and P2Y12), showing distinct inflammatory roles across acute and sustained responses. Furthermore, Pattern Recognition Receptors (PRRs), including Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4), were examined for their role in responses to pathological aggregates like α-synuclein fibrils, common in neurodegenerative conditions. This study elucidates the receptor-specific mechanisms underlying microglial activation and cytokine production by simulating neuroinflammatory conditions, advancing our understanding of the molecular pathways central to disease progression. To achieve these, PBMCs were differentiated into microglia-like cells through a standardised protocol, optimised to yield cells expressing validated microglial markers, such as ionised calcium-binding adapter molecule 1 (Iba1), purinergic receptor P2Y12 (P2RY12), and transmembrane protein 119 (TMEM119). Functional assays, including cytokine profiling and phagocytosis, confirmed the cells’ responsiveness to neuroinflammatory stimuli, closely replicating primary microglial behaviours. This model enabled an in-depth investigation into receptor-specific inflammatory pathways by using real-time quantitative PCR, cytokine assays, and transcriptomic analyses, revealing interactions with pathological aggregates like α-synuclein fibrils. A major contribution of this research lies in evaluating transient receptor potential (TRP) channels, specifically transient receptor potential vanilloid 4 (TRPV4), as modulators of inflammation in microglia. Pharmacological activation of TRPV4 with GSK1016790A (GSK101) significantly reduced pro-inflammatory cytokine production (e.g., interleukin-1 beta [IL-1β], tumour necrosis factor-alpha [TNF-α]) in ATP-stimulated microglia while concurrently upregulating nuclear receptor subfamily 4 group A member 2 (Nurr1), an orphan nuclear receptor associated with neuroprotective and anti-inflammatory effects. This dual effect demonstrates that TRPV4 activation mitigates inflammatory responses and promotes a neuroprotective microglial phenotype, suggesting a promising therapeutic target for neuroinflammation-driven diseases. The TRPV4-Nurr1 axis modulation established here paves the way for future investigations into its role as a therapeutic approach, with broad implications for neuroinflammatory diseases such as Parkinson’s and Alzheimer’s. In conclusion, this thesis introduces a robust and scalable human-derived microglia model that captures human-specific inflammatory responses and receptor interactions observed in neurodegenerative diseases. This work elucidates the roles of DAMPs, P2 receptors, and TRPV4 in microglial activation, providing a foundation for developing therapeutic strategies targeting neuroinflammation. The findings suggest the potential of the TRPV4-Nurr1 pathway for managing neuroinflammation in neurodegenerative diseases.